Spowiedź życia mojego : Dzienniki Karola Estreichera Seniora z lat 1847-1905 - Karol Estreicher (Księgarnia Akademicka Publishing, 2024)
MY LIFE’S CONFESSION: KAROL ESTREICHER SR.’S DIARIES FROM THE YEARS 1847-1905 The diaries of Karol Estreicher Sr. for the years 1847-1905 originate from the Estreicher family’s estate preserved at the Kraków Society of Friends of the Fine Arts. They comprise two sections: unedited manuscripts (First Book, from 15 August 1847 to 2 June 1849; Third Book, from 8 June 1849 to 12 March 1850) and typescripts (from 9 December 1847 to 10 February 1849; from 16 March 1850 to 29 August 1905) prepared for publication by the bibliographer’s daughter, Maria Estreicher, in the first half of the 20th century. Currently, the documents have been transcribed and combined into a single collection. Existing annotations have been modernised, expanded, and supplemented with new ones, creating a compendium of over 2,500 explanations of factual, bibliographical, biographical, geographical, lexical, and other details. Among the daily entries, one also finds copies of private and official letters, and library reports, which were included in the diaries by Karol Estreicher himself. They provide a compelling addition to the memoirs. From a chronological point of view, the entire collection spans 58 years of the author’s life and is divided according to his place of residence into Lviv, Warsaw, and Kraków periods. It includes events significant for the history of the Estreicher family, as well as depictions of the literary, theatrical, scholarly, and political life of the time.